2020
DOI: 10.3390/pathogens9080605
|View full text |Cite
|
Sign up to set email alerts
|

Control of Persistent Salmonella Infection Relies on Constant Thymic Output Despite Increased Peripheral Antigen-Specific T Cell Immunity

Abstract: Recent thymic emigrants are the youngest subset of peripheral T cells and their involvement in combating persistent bacterial infections has not been explored. Here, we hypothesized that CD4+ recent thymic emigrants are essential immune mediators during persistent Salmonella infection. To test this, we thymectomized adult mice either prior to, or during, persistent Salmonella infection. We found that thymic output is crucial in the formation of protective immune responses during the early formation of a Salmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…S. Typhimurium persistently infects Slc11a1 +/+ mice [ 4 , 152 , 153 ] and CD4 + and CD8 + T cells [ 85 ] and IFNγ [ 4 ] are important in final clearance and IL-17 is also thought to be important [ 153 ]. Persistent infection in the spleen is associated with elevated numbers of neutrophils, dendritic cells and macrophages but with no increase in T cells [ 153 , 154 ]. These authors showed that CD8alpha+ DC and Gr-1+ cells (neutrophils) increased in the red pulp.…”
Section: Is There Anything Characteristic To the Immune Response During Persistent Infections?mentioning
confidence: 99%
“…S. Typhimurium persistently infects Slc11a1 +/+ mice [ 4 , 152 , 153 ] and CD4 + and CD8 + T cells [ 85 ] and IFNγ [ 4 ] are important in final clearance and IL-17 is also thought to be important [ 153 ]. Persistent infection in the spleen is associated with elevated numbers of neutrophils, dendritic cells and macrophages but with no increase in T cells [ 153 , 154 ]. These authors showed that CD8alpha+ DC and Gr-1+ cells (neutrophils) increased in the red pulp.…”
Section: Is There Anything Characteristic To the Immune Response During Persistent Infections?mentioning
confidence: 99%
“…We showed a high diversity of TREC and KREC levels in all groups. Patients with CAP had the increased levels of TRECs compared to controls, which probably reflects the protective production of the thymus as an early response to infection [ 34 ]. These data are consistent with the findings of Cuvelier et al, who showed the protective reactive thymus hyperplasia and increased TRECs as a proxy for thymic output in adult patients with COVID-19 [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…They also produced far more of the immunoregulatory cytokine IL-10 compared to lymphoid CD4 + T cells, which were more likely to produce IFN-g. In addition, lack of thymic output prior to persistent S. Typhimurium infection results in a loss of control over infection, despite the fact that Salmonella specific CD4 + T cells are elevated (Goggins et al, 2020). It will be important to explore whether the thymus contributes more T cells to the lymphoid compartment or the hepatobiliary tissue.…”
Section: Salmonella Typhimurium Microbial Pathogenesis and Immune Evasion Of The Hepatobiliary Systemmentioning
confidence: 99%